2007
DOI: 10.1007/s00595-006-3343-1
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Cocoon in an Aged Man: Report of a Case

Abstract: An abdominal cocoon is an extremely rare condition, which has been mainly reported in young adolescent women as a cause of small bowel obstruction. In these patients the small bowel is encased in a fibrous sac called an abdominal cocoon. We herein describe a 74-year-old man who demonstrated an abdominal cocoon without having any history associated with an abdominal cocoon. A laparotomy showed bloody ascites and the entire small bowel was encased in a thin white fibrous membrane like a cocoon. The small intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…AC has classically been described in young adolescent girls from tropical and subtropical countries, although adult cases have been reported from temperate zones as well [9,12,[26][27][28]. However, because this condition has also affected men, premenopausal women, and children, there seems to be little support for these theories [7,9,29]. Results from our study with large number of patients indicated that most of the ACs in the Chinese population occur in male adults, which is in contrast to some of the the data reported by others [9,12,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AC has classically been described in young adolescent girls from tropical and subtropical countries, although adult cases have been reported from temperate zones as well [9,12,[26][27][28]. However, because this condition has also affected men, premenopausal women, and children, there seems to be little support for these theories [7,9,29]. Results from our study with large number of patients indicated that most of the ACs in the Chinese population occur in male adults, which is in contrast to some of the the data reported by others [9,12,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal cocoon (AC), also known as sclerosing encapsulating peritonitis (SEP) [1,2], is a relatively rare cause of intestinal obstruction [3][4][5][6][7][8][9]. First described by Foo et al [10,11], it is characterized by complete or partial encasement of the small bowel by a fibrocollagenous cocoon-like membrane.…”
Section: Introductionmentioning
confidence: 99%
“…2 The primary or the idiopathic form is seen characteristically in young adolescent girls of 4-18 year age group from the tropical or subtropical countries. 3 The more common secondary form is associated with prolonged beta blocker therapy, local irritation of the peritoneum by trauma, peritoneal dialysis, peritoneal-venous shunting, and ventriculoperitoneal shunt.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal cocoon is an extremely rare cause of small bowel obstruction; it has been reported in previous literature to occur mainly in young adolescent women. 1 However, a more recent study done in China showed that abdominal cocoon occurred mostly in Chinese men (87.7%), in the 65 patients who were studied. 2 …”
Section: Discussionmentioning
confidence: 91%
“…Abdominal cocoon on the other side was first described in 1978 by Foo et al 4 It refers to a rare condition where there is either total or partial encasement of the small bowel by a fibrocollagenous sac, which looks like a cocoon. 1 …”
Section: Discussionmentioning
confidence: 99%